Pemberdayaan Kelompok Budidaya Ikan di Kelurahan Sungai Lulut melalui Teknologi Pembuatan Pakan Herbal Daun Kelor dan Edukasi Ikan sebagai Nutraseutikal Pencegah Stunting: The Driving Force of Fish Farming Group in Sungai Lulut Village through the Technology of Herbal Moringa Leaf Feed Production and Education on Fish as a Nutraceutical to Prevent Stunting - Niah, Rakhmadhan; Prihandiwati, Erna; Aisyah, Noor; Dharmaji, Deddy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The issue